ANALISIS DAYA TARIK OBJEK WISATA PANTAI PASER PUTIH DI DESA JIKUMERSA KECAMATAN LILIALY KABUPATEN BURU - Lasmana Muhajirin Ode Rabani; Yosevita Theodora Latupapua; Merlin Renny Sitanala (Jurnal Sylva Scienteae, 2024)
This research aims to determine the attractiveness of the Paser Putih beach tourist attraction, to find out visitors' perceptions of the Paser Putih beach tourist attraction in Jiku Felt Village, Lilialy District, Buru Regency. This research uses observation and interview methods using questionnaires given to visitors accidentally (accidental sampling), documentation, and literature studies which are analyzed descriptively qualitatively. The results of this research show that the attractiveness of the Paser Putih beach tourist attraction includes 7 assessment criteria, namely beauty, beach safety/security, type and color of sand, environmental cleanliness, variety of activities, beach width and comfort. The purpose of this research is to get the value of the attractiveness of the Paser Putih beach tourist attraction because this beach has an attractive beauty such as white sand, bluish sea, beach views, you can see the mountains, the downstream of Lake Jikumerasa and the presence of a park further adds to the attraction. Paser Putih beach. The distance of the tourist attraction from the city center is 15 km and takes approximately 15 minutes. The Paser Putih beach area received a score of 83% worthy of being developed as a tourist attraction.